2018
DOI: 10.1177/2309499018802484
|View full text |Cite
|
Sign up to set email alerts
|

Risk of patella baja after opening-wedge high tibial osteotomy

Abstract: Medial opening-wedge high tibial osteotomy (OWHTO) induces a lower patellar position, and the subsequent degree of patellar movement may not be predicted preoperatively. The purpose of this study was to clarify the relationship between preoperative and postoperative patellar height based on the correction angle of OWHTO and to create a formula to predict the appearance of patella baja following OWHTO. Materials and Methods: Seventy-five knees with varus knee osteoarthritis treated with OWHTO were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
(46 reference statements)
2
26
0
Order By: Relevance
“…In many studies, the correction angle of the weight-bearing line in OWHTO is considered to be related to the change in patella height and the deterioration of the patellofemoral joint. Otsuki et al [ 4 ] found that for every 1° increase in the correction angle, the CDI decreased by 1.7%, and CDI < 0.8 was a risk factor for the occurrence of a low patella after surgery. Yoon et al [ 2 ] conducted a cohort study of 135 patients who had undergone OWHTO with an average of 52 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, the correction angle of the weight-bearing line in OWHTO is considered to be related to the change in patella height and the deterioration of the patellofemoral joint. Otsuki et al [ 4 ] found that for every 1° increase in the correction angle, the CDI decreased by 1.7%, and CDI < 0.8 was a risk factor for the occurrence of a low patella after surgery. Yoon et al [ 2 ] conducted a cohort study of 135 patients who had undergone OWHTO with an average of 52 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patellofemoral joint on the sagittal plane is also influenced by the operation [2]. Several studies have shown that OWHTO causes patellar infera, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more difficult for total knee arthroplasty to be performed in the future [3][4][5][6][7][8]. Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, the correction angle of the weightbearing line in OWHTO is considered to be related to the change in patella height and the deterioration of the patellofemoral joint. Otsuki et al [4] found that for every 1° increase in the correction angle, the CDI decreased by 1.7%, and CDI < 0.8 was a risk factor for the occurrence of a low patella after surgery. Yoon [2] et al conducted a cohort study of 135 patients who had undergone OWHTO with an average of 52 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patellofemoral joint on the sagittal plane is also in uenced by the operation [2] . Several studies have shown that OWHTO causes patella infra, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more di cult for total knee arthroplasty to be performed in the future [3][4][5][6][7][8] . Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of PFJOA is linked to abnormal patellar kinematics, which catalyzes its initiation. Patella baja is defined as a short patellar tendon and is often caused by complex regional pain syndrome [59], trauma, immobilization or surgical procedures such as an opening wedge high tibial osteotomy [60]. Patellar misalignment caused by patella baja changes the patellofemoral contact pressure, increasing the joint reactive forces on both the patella and trochlea.…”
Section: Discussionmentioning
confidence: 99%